A Neurocomputational account of the role of contour facilitation in brightness perception - Domijan, Dražen (Frontiers in Human Neuroscience, 2015)
A novel filling-in model is proposed in order to account for challenging brightness illusions where inducing background elements are spatially separated from gray target such as dungeon, cube and grating illusion, bull's eye and ring patterns. The model implements simple idea that neural response to low-contrast contour is enhanced (facilitated) by the presence of collinear or parallel high-contrast contour in the wider neighborhood. Contour facilitation is achieved via dendritic inhibition which enables computation of maximum function among inputs to the node. Recurrent application of maximum function leads to the propagation of neural signal along collinear or parallel contour segments. When strong global contour signal is accompanied with weak local contour signal at the same location, conditions are met to produce brightness assimilation within filling-in network. Computer simulations showed that the model correctly predicts brightness appearance in all of the above mentioned illusions as well as in White's effect, Benary's cross, Todorović's illusion, checkerboard contrast, contrast-contrast illusion and various variations on the White's effect. The proposed model offer new insights on how geometric factors (contour colinearity or parallelism) jointly with contrast magnitude contribute to the brightness perception.